Flavonoid and Steroids from Polygonum viscosum (Bangladesh Pharmaceutical Journal, 2016)
Repeated chromatographic separation and purification of the n-hexane-ethyl acetate (3:1) extract of aerial parts of Polygonum viscosum provided a flavonoid- ternatin (1) and two steroids- stigmasterol (2) and stigmasta-4,22-dien-3-one (3). The structure of these compounds were determined on the basis of extensive NMR and other spectroscopic techniques and comparison with published data. The identity of steroids 2 and 3 was confirmed by co-TLC with authentic sample.Bangladesh Pharmaceutical Journal 19(2): 166-169, 2016